Aridification Shaped the Diversification of Bothriembryon Land Snails in a Global Biodiversity Hotspot - Frank Köhler; Corey S. Whisson; Nerida G. Wilson; Andrew M. Hosie; Abraham S. H. Breure; Lisa A. Kirkendale (Journal of Biogeography, 2025)
Aim Resolving the spatio‐temporal diversification patterns and systematic relationships of endemic Australian land snails against the backdrop of Neogene aridification through analyses of a combined nuclear and mitochondrial DNA sequence dataset. Location Western Australia. Taxon Mollusca, Stylommatophora, Bothriembryontidae, Bothriembryon. Methods We employed Bayesian Inference and Maximum Likelihood to reconstruct the phylogenetic relationships in a group of Australian land snails using mitochondrial (COI, 16S) and nuclear (ANT) DNA sequences. Divergence times have been estimated by employing optimised molecular clocks using BEAST2, and RelTime in MEGA12. Speciation and net‐diversification rates have been modelled using revBayes to visualise diversification dynamics in lineage‐through‐time (LTT) plots. We employed automated species delimitation methods ASAP and bPTP to estimate taxonomic diversity. Results Our final sequence dataset contained 1052 new DNA sequences from 374 individuals, representing 97% of all accepted species plus 26 putatively new species based on morphology and distribution. Recognizing almost three times as many candidate species, both DNA‐based species delimitation methods have excessively inflated diversity estimates, casting doubt on the usefulness of these methods in groups with marked phylogeographic structure. Nine well‐supported principal clades were recovered. Fossil‐calibrated chronograms revealed an early bifurcation of Bothriembryon followed by an accumulation of lineages over time. LTT plots revealed a relative flattening of the speciation curve from 15 to 10 Ma on. However, we also detected a steep increase in intraspecific lineage diversification during the last approx. 1 Ma. The modeled speciation and net diversification rates have continuously declined over the last 25 Ma, while extinction rates have remained relatively steady until about 5 Ma, when they also started to climb. Main Conclusions Declining diversification rates during much of the Neogene, followed by increasing extinction rates, coincided with increasing aridity throughout Western Australia. A more recent increase in lineage diversification rates, driven by intraspecific differentiation, coincides with the rise of mesic conditions since the end of the Pleistocene. Both trends imply that through influencing extinction and diversification rates, historical climate change has likely contributed to shaping the current distribution patterns in Bothriembryon land snails that are characterised by fragmentation. Moreover, by uncovering many undescribed taxa, including multiple short‐range endemics, this study highlights the importance of continued conservation efforts in this globally important biodiversity hotspot. Key habitats, such as lithorefugia, in an otherwise harsh and exposed landscape are important strongholds for Bothriembryon to weather the impact of aridification.

Phylogenetic assessment of the halophilic Australian gastropod Coxiella and South African Tomichia resolves taxonomic uncertainties, uncovers new species and supports a Gondwanan link - Angus D'Arcy Lawrie; Jennifer Chaplin; Lisa Kirkendale; Corey Whisson; Adrian Pinder; Musa C. Mlambo (Molecular Phylogenetics and Evolution, 2023)

Video surveys of sea snakes in the mesophotic zone shed light on trends in populations - Conrad W. Speed; Nerida G. Wilson; Ruchira Somaweera; Vinay Udyawer; Mark G. Meekan; Corey Whisson; Karen Miller (Frontiers in Marine Science, 2022)
Declines in abundance of sea snakes have been observed on reefs throughout the Indo-Pacific, although the reasons are unknown. To date, surveys have occurred on shallow reefs, despite sea snakes occurring over a large depth range. It is not known if populations of sea snakes in deep habitats have undergone similar declines. To address this, we analysed deep-water video data from a historical hotspot of sea snake diversity, Ashmore Reef, in 2004, 2016, and 2021. We collected 288 hours of video using baited remote underwater videos and a remotely operated vehicle at depths between 13 and 112 m. We observed 80 individuals of seven species with Aipysurus laevis ( n = 30), Hydrophis peronii ( n = 8), and H. ocellatus ( n = 6) being the most abundant. Five of the species ( A. duboisii , A. apraefrontalis , H. ocellatus , H. kingii , and Emydocephalus orarius ) had not been reported in shallow waters for a decade prior to our study. We found no evidence of a decline in sea snakes across years in deep-water surveys, although abundances were lower than those in early shallow-water surveys. A comparison of BRUVS data from 2004 and 2016 was consistent with the hypothesis that predation by sharks may have contributed to the loss of sea snakes in shallow habitats. Our study highlights the use of underwater video to collect information on sea snakes in the mesophotic zone and also suggests that future monitoring should include these depths in order to capture a more complete representation of habitats occupied.

A tropical Australian refuge for photosymbiotic benthic fauna - Zoe T. Richards; Rodrigo Garcia; Glenn Moore; Jane Fromont; Lisa Kirkendale; Monika Bryce; Clay Bryce; Ana Hara; Jenelle Ritchie; Oliver Gomez; Corey Whisson; Mark Allen; et al. (Coral Reefs, 2019)